MO923: Electronic Medication Record Accuracy and Clinical Pharmacist Intervention in Haemodialysis Outpatient Settings. (3rd May 2022) - England, Gillian; Davin, Dawn; Lavin, Peter; Wall, Catherine; Deasy, Evelyn; Mellotte, George J
Abstract: BACKGROUND AND AIMS: Haemodialysis (HD) units in Ireland operate a national electronic Kidney Disease Clinical Patient Management System (KDCPMS). KDCMPS is not always used as the primary electronic patient record (EPR) but in conjunction with other electronic and paper record systems across the healthcare setting. HD patients on average have 6 comorbidities and have the largest pill burden for any chronic disease; consuming 19 oral doses/day, comprising of 12 different medicines [1, 2]. Frequent medication changes, polypharmacy, comorbidities and non-adherence, increase the risk of drug-related problems (DRPs). In the HD population, DRPs are prevalent at a rate of 1 for every three medication exposures and can elicit negative outcomes, including worsening morbidity, mortality and increased healthcare expenditure [3]. In this study setting, KDCPMS information accuracy has not been examined to date. This study aims to describe medication discrepancies within KDCPMS records of HD outpatients. METHOD: This prospective, observational study was conducted in the HD unit of Tallaght University Hospital, Dublin. Medicine reconciliation was conducted to identify KDCPMS discrepancies, followed by medication review to document DRPs. Recommendations were issued by the clinical pharmacist to resolve DRPs. RESULTS: All KDCPMS records examined contained intentional and unintentional discrepancies ( n  = 36). Unintentional discrepancies corresponding to 8.8 discrepancies per patient (5.13SD) were observed. A total of 143 DRPs were identified in 34 patients (94.4%) (Table 1 ). Out of these, 65% of pharmacist recommendations were accepted ( n  = 93), 22.4% were rejected ( n  = 32), 8.4% ( n  = 12) were referred to the renal multidisciplinary team (MDT) and 4.2% were not actioned ( n  = 6). Discrepancies and DRPs by therapeutic area are shown in Fig. 1 . Parenteral anticoagulants and thrombolytics were the most common undocumented intentional discrepancies (48.6%, n  = 50/103) followed by iron (32%, n  = 33/103). A total of 16 (44.4%) patients had at least one medicine de-prescribed. New prescriptions were issued for 26 patients (72.2%) for 81 medicines. CONCLUSION: KDCPMS contains inaccuracies that could lead to systemic error. Robust clinical governance supported by the national policy is required to improve the accuracy of information contained in KDCPMS and support its use as the primary platform for renal patients. Specialist clinical pharmacists working collaboratively within the renal MDT reduce discrepancies, improve KDCPMS accuracy and resolve DRPs. Enhanced pharmaceutical care by specialist pharmacists should be supported within national models of care for chronic disease management to enhance patient outcomes.